Portuguese version of the Tilburg Frailty Indicator: Transcultural adaptation and psychometric validation - Coelho, Tiago (2015)
To present the translation and validation process of the Portuguese version of the Tilburg Frailty Indicator (TFI). A cross-sectional study was designed using a non-probability sample of 252 community-dwelling older adults. Preliminary studies were carried out for face and content validity assessment. Internal consistency, test–retest reliability, construct (convergent/divergent) and criterion validity were subsequently analyzed. The sample was mainly women (75.8%), with a mean age of 79.2 ± 7.3 years. TFI internal consistency was good (KR-20 = 0.78). Test–retest reliability for the total was also good (r = 0.91), with kappa coefficients showing substantial agreement for most items. TFI physical and social domains correlated as expected with concurrent measures, whereas the TFI psychological domain showed similar correlations with other psychological and physical measures. The TFI showed a good to excellent discrimination ability in regard to frailty criteria, and fair to good ability to predict adverse outcomes. The psychometric properties of the TFI seem to be consistently good. These findings provide initial evidence that the Portuguese version is a valid and reliable measure for assessing frailty in the elderly.